Thermoelastic effects in the contact mechanics of 1D+1D rough profiles. (15th October 2022) - Afferrante, L.; Carbone, G.; Putignano, C.; Violano, G.; Demelio, G.
Abstract: Rough contact mechanics is a challenging topic that has attracted the interest of many scientists in the past and recent years. Notwithstanding a large amount of literature on the topic, there is a lack of studies investigating the contact behaviour of rough elastic bodies exchanging heat at the interface. For this reason, we propose a deterministic model to investigate the thermoelastic contact of a linear elastic half-plane indented by a rigid rough punch. Surprisingly, an increase in the temperature difference between the contacting solids does not change the relationship between contact area and load as well as that between interfacial mean separation and load. However, the thermal expansion causes an increase in the force required to sustain the contact at a given penetration. In addition, thermal contact resistance (TCR) is predicted to be a decreasing function of the contact pressure in agreement with the trend suggested by experimental data available in the literature. On the contrary, the dependence on the temperature difference Δ T seems to be strictly related to the characteristics of the materials and, for the elastic case investigated in this work, TCR is found to be almost independent of Δ T .